The London and country brewer : containing the whole art of brewing all sorts of malt-liquors, as practised both in town and country, according to observations made by the author in four years travels through the several counties in England, also the method of preserving liquours in the cask and directions to be observed in bottling them, In three parts to which is added a supplement.: containing the whole art of brewing all sorts of malt-liquors, as practised both in town and country, according to observations made by the author in four years travels through the several counties in England, also the method of preserving liquours in the cask and directions to be observed in bottling them, In three parts to which is added a supplement. (2012) - Unknown
No abstract available